Levodopa treatment patterns in Parkinson's disease: A retrospective chart review. (2022) - Navaratnam, Prakash; Arcona, Steve; Friedman, Howard S.; Leoni, Matthew; Sasane, Rahul
Highlights: Patients initiating monotherapy with levodopa-PDDI for PD have frequent treatment changes. Patients who stop levodopa-PDDI generally restart it within the same year. Patients with less severe disease start with lower levodopa doses than those with more severe disease. Abstract: Background: Medication regimens for Parkinson's disease (PD) may change as the disease progresses, symptoms fluctuate, or medication-related adverse events occur. This study evaluated treatment trends by observation year for patients initially receiving monotherapy with levodopa and a peripheral dopa decarboxylase inhibitor (PDDI). Methods: In this retrospective chart review, therapy changes were evaluated for patients across the US diagnosed with PD on or before 6/30/2014 who initially received levodopa-PDDI monotherapy. Index date was the first clinic visit. Post-index was any time between the first 31 days after index and study end (6/30/2019). Index Hoehn-Yahr (H-Y) score and medication changes were also analyzed by index low (<400 mg/day) or high (≥400 mg/day) levodopa doses in the levodopa-PDDI combinations. Results: In the levodopa-PDDI cohort (n = 95), there were 0.39 dose escalations, 0.16 dose reductions, 0.12 discontinuations, 0.19 therapy switches, and 0.24 add-ons per patient per year during the study. Most dose escalations or add-ons occurred within the first 6 months post-index. Of those who ever stopped levodopa-PDDI (n = 34), 31 (91%) restarted within the study period. Most (83%) patients who restarted levodopa-PDDI did so in the same year as stopping treatment. Index low dose users were associated with lower H-Y scores, were more inclined to escalate their dose, and were less inclined to reduce their dose in the first 2 years of treatment than index high dose users. Conclusions: Prescribers and patients tend to experiment with levodopa-PDDI treatment. Although many patients appeared to stop levodopa-PDDI after an initial course of treatment, most subsequently restarted treatment.